Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Very little in situ produced radiocarbon retained in accumulating Antarctic ice - van der Kemp, Wybe J.M.; Alderliesten, Cees; van der Borg, Klaas; Holmlund, Per; de Jong, Arie F.M.; Karlöf, Lars; Lamers, R.A.N.; Oerlemans, Johannes; Thomassen, Martijn P.A.; van de Wal, Roderik S.W. (8th International Conference on Accelerator Mass Spectrometry, 2000)
Ice samples from Dronning Maud Land, Antarctica, were analyzed for 14CO2 and 14CO by accelerator mass spectrometry. Only a small amount (∼2%) of in situ produced radiocarbon was detected. The calibrated radiocarbon ages, corrected for in situ produced 14C, are in fair agreement with age estimates obtained from stratigraphical methods added to a gas inclusion model. The ages of the entrapped air range from recent to ca. 1200 AD.
Keywords: Dronning Maud Land; fysikk; karbondatering; karbondioksid; kjemi; massespektrometri